Numerical fatigue assessment of welded and HFMI-treated joints by notch stress/strain and fracture mechanical approaches. (June 2018) - Leitner, Martin; Simunek, David; Shah, Syed Faheem; Stoschka, Michael
Abstract: Post-treatment methods enhance the fatigue strength of welded high-strength steel joints significantly. In industrial applications, one commonly applied technique is the high frequency mechanical impact (HFMI) treatment. Attained local benefits increasing fatigue strength are the compressive residual stress state, the reduced notch effect at the weld toe, and additionally the local work hardening of the material. This paper presents the set-up of a closed simulation loop including structural weld simulation, numerical computation of the HFMI-process, and a numerical evaluation of the local fatigue life. A thermo-mechanical coupled weld process simulation using Sysweld is built-up to assess the course of residual stress and strain due to welding. The resulting local material behavior is transferred as mechanical cards to the solver Abaqus for the subsequent numerical simulation of the HFMI-process. Hence, major influences such as transient change of material parameters during welding and subsequent cool-down, effect of process dependent clamping conditions and changing contact characteristics are considered. Finally, a numerical evaluation of the local fatigue behavior by the local stress/strain approach and by crack propagation is performed by the aid of the software packages Femfat, nCode and Franc2D . A comparison of the simulated fatigue life with experimental test results proofs their basic applicability; but also numerical limitations of the presented simulation tools are determined. The major benefit of the established simulation chain is the opportunity to study different weld process and HFMI-treatment parameters in regard to fatigue strength without the need of comparably expensive fatigue tests.